Self-assembled 3D Fe2(MoO4)3 microspheres with amorphous shell as anode of lithium-ion batteries with superior electrochemical performance. (18th May 2020) - Su, Yun; Chen, Shuangqiang; Yang, Qinsi; Wang, Yong
Graphical abstract: Self-assembled 3D Fe2 (MoO4 )3 microspheres with a thin amorphous shell and inner voids, synthesized by a morphology-tunable and template-free hydrothermal method, exhibited highly reversible capacity and superior cycling stability as anode of lithium ion batteries. Highlights: Fe2 (MoO4 )3 spheres with amorphous shells and tunable morphologies were prepared. FMO-A has delivered high reversible capacities and remarkable rate performances. FMO-A have isotropic feature, low Gibbs free energy and low grain boundary. Abstract: Metal molybdates are regarding as promising electrode materials for next-generation lithium-ion batteries (LIBs). However, the poor electronic conductivity and sluggish ion diffusion are the two main obstacles that limit their electrochemical performances. In this work, self-assembled hierarchical Fe2 (MoO4 )3 microspheres with a thin amorphous shell (FMO-A) were prepared via a morphology-tunable and template-free hydrothermal method as an example of metal molybdates for LIBs. The morphologies were easily tunable by changing experimental parameters, such as the pH value, and reaction time. When applied as anode of LIBs, FMO-A delivered a high reversible capacity of 1138.2 mAh g −1 after 250 cycles at 100 mA g −1 and displayed remarkable rate performances. This is mainly ascribed to the unique hierarchical structure and high surface area of Fe2 (MoO4 )3 and the thin amorphous shell on providing low Gibbs free energy on redox reactions, reduced grain boundaries, isotropic nature, and buffering volume variations during cycles.